특정용제 Target 형 활성금속첨착 활성탄소섬유의 개발 - 최강용(Kang Yong Choi); 김광수(Kwang Su Kim); 김태원(Tae Won Kim); 전민기(Min Kee Jun); 박해경(Hea Kyung Park) (Daehan hwan'gyeong gonghag hoeji, 2013)
To acquire enhanced adsorption capacity for especially targeted VOCs, activated carbon fiber of which surface area was $1,100m^2/g$ was selected and active metals were loaded. After screening study, Cr and Cu were selected as a base metal for improving adsorption capacity of activated carbon fiber. For acquiring better performance, metal loading, loading temperature, loading hours and kinds of loaded metals were changed as preparing variables. Properties measurement and adsorption capacity evaluation were performed. We found that the best conditions for metal loading were 5 hours loading at $100^{°}C$ and the adsorption capacity was enhanced almost double. Also we confirmed that more than 0.5 seconds contact time is needed for best adsorbate diffusion and adsorption over activated carbon fiber. 기존 흡착제들보다 우수한 흡착성능을 확보하고, 특히 특정한 용제에 대한 흡착성능을 극대화하기 위하여 $1,100m^2/g$의 비표면적을 갖는 활성탄소섬유를 기본흡착제로 적용하였고, 여기에 활성금속을 첨착시켜 흡착성능과 선택성을 제고하고자 하였다. 활성금속은 screening 연구를 수행하여 최종적으로 Cu, Cr을 선정하였으며, 활성금속첨착 활성탄소섬유의 제조변수는 제조온도, 제조시간, 활성금속의 종류이었다. 물성측정 및 흡착반응실험을 통하여 금속을 $100^{°}C$에서 5시간 동안 첨착하였을 경우 acetone gas 흡착성능이 가장 높게 나타났으며, 기존 활성탄소섬유보다 2배 이상의 높은 흡착성능을 확인하였다. 한편, 활성금속첨착 활성탄소섬유의 확산 및 흡착에 필요한 최소 접촉시간은 최소한 0.5초 이상은 유지해야 함을 확인할 수 있었다.